Improving Energy Literacy Using the Problem-Based Learning (PBL) Model for Grade VI Students - Suratmi; Riswan Jaenudin; Muhamad Yusup; Sardianto Markos Siahaan; Khoirul Rodzikin (Jurnal Elementaria Edukasia, 2025)
This study aims to improve the learning outcomes of students in class VI.A SD Negeri 4 Palembang on Energy Literacy material through the application of the Problem Based Learning (PBL) learning model. This research used the Classroom Action Research method carried out in two cycles, involving 23 students. Data were collected through observation, tests, and documentation to evaluate the effectiveness of the application of the learning model. The PBL model is designed to improve energy literacy by actively involving learners in solving problems relevant to everyday life, so that learning becomes more meaningful and contextual. Each cycle includes planning, action implementation, observation and reflection to ensure continuous improvement. The results showed significant improvements in the understanding of energy literacy concepts, learning outcomes, and critical thinking skills of learners. They became more active, enthusiastic and showed deeper engagement in the learning process. In addition, learners also showed an increased ability to connect energy literacy concepts with everyday phenomena, making learning more relevant. This study concludes that the implementation of the PBL model can improve students' energy literacy. The researcher recommends the use of PBL model as an alternative strategy to be applied in other classes, because it is proven to be able to encourage active, creative, and relevant learning. This strategy is expected to have a positive impact in improving the quality of education, especially at the elementary school level.